2013
DOI: 10.3892/or.2013.2266
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant methylation of LINE-1, SLIT2, MAL and IGFBP7 in non-small cell lung cancer

Abstract: Genome-wide DNA hypomethylation and gene hypermethylation play important roles in instability and carcinogenesis. Methylation in long interspersed nucleotide element 1 (LINE-1) is a good indicator of the global DNA methylation level within a cell. Slit homolog 2 (SLIT2), myelin and lymphocyte protein gene (MAL) and insulin-like growth factor binding protein 7 (IGFBP7) are known to be hypermethylated in various malignancies. The aim of the present study was to assess the precise methylation levels of LINE-1, SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 30 publications
6
34
0
Order By: Relevance
“…Increased LOH and methylation of the MALL gene was observed. This is consistent with previous reports in which MAL promoter hypermethylation was detected in cervical disease [21, 22] as well as several cancers, including non-small cell lung cancer [23], head and neck squamous cell carcinoma [19], cervical cancer [20, 24], ovarian cancer [25], gastric cancers [26], and colorectal cancer [27]. However, further detailed analyses of the mechanisms of MALL downregulation are necessary to examine whether LOH and methylation are cooperative events or different mechanisms as well as to determine if these events are found in the majority of colon and rectal cancers or only specific subsets.…”
Section: Discussionsupporting
confidence: 94%
“…Increased LOH and methylation of the MALL gene was observed. This is consistent with previous reports in which MAL promoter hypermethylation was detected in cervical disease [21, 22] as well as several cancers, including non-small cell lung cancer [23], head and neck squamous cell carcinoma [19], cervical cancer [20, 24], ovarian cancer [25], gastric cancers [26], and colorectal cancer [27]. However, further detailed analyses of the mechanisms of MALL downregulation are necessary to examine whether LOH and methylation are cooperative events or different mechanisms as well as to determine if these events are found in the majority of colon and rectal cancers or only specific subsets.…”
Section: Discussionsupporting
confidence: 94%
“…IGFBP-7 may play a tumor-suppressor role in carcinogenesis of these cancers, mainly through inactivation of its DNA methylation [22-25]. DNA methylation is involved in the regulation and expression of genes [26].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, LINE-1 hypomethylation was reported to be related to worse prognosis of NSCLC, and the methylation rate was significantly lower in squamous cell carcinoma than in AD [18,19]. Squamous cell carcinoma and AD are the 2 major histologic subtypes of NSCLC, and their pathogenesis and clinical behavior are different.…”
Section: Commentmentioning
confidence: 95%